Receptor-Mediated NETosis on Neutrophils - Chen, Tao; Li, Yanhong; Sun, Rui; Hu, Huifang; Liu, Yi; Herrmann, Martin; Zhao, Yi; Muñoz, Luis E. (Frontiers in Immunology, 2021)
Neutrophil extracellular traps (NETs), a web-like structure containing chromatin, have a significant role in assisting capture and killing of microbes by neutrophils during infection. The specific engagement of cell-surface immunoreceptors by extracellular signaling molecules activates diverse intracellular signaling cascades and regulates neutrophil effector functions including phagocytosis, reactive oxygen species release, degranulation, and NET formation. However, overproduction of NETs is closely related to the occurrence of inflammation, autoimmune disorders, non-canonical thrombosis and tumor metastasis. Therefore, it is necessary to understand neutrophil activation signals and the subsequent formation of NETs, as well as the related immune regulation. In this review, we provide an overview of the immunoreceptor-mediated regulation of NETosis. The pathways involved in the release of NETs, during infection or stimulation by noninfectious substances are discussed in detail. The mechanisms by which neutrophils undergo NETosis help to refine our views on the roles of NETs in immune protection and autoimmune diseases, providing a theoretical basis for research on the immune regulation of NETs.